Competitive Strategies of ICICI Prudential Life Insurance— An Inclusive Analysis - Barathi, C; Meitei, Ch. Ibohal (Journal of Commerce and Trade, 2011)
ICICI Prudential Life Insurance which was the market leader among the private life insurers for the period 2000-2009, has been witnessing erosion of its market share coupled with huge amount of accumulated losses. The business performance of the company has been encouraging with both the gross premium, new business premium and renewal premium growing at a steady pace. The company offers a wide bouquet of products catering to the needs of different target segments and has been a pioneer in leveraging technology to provide services according to varied customer needs. With the impending growth of competitive pressures due to the imminent entry of new players in the industry, the need was felt to analyse the competitive strategies adopting by the company so as to understand its strengths and areas requiring managerial focus. The researcher has relied on secondary data in order to identify and analyse the competitive strategies adopted by the company during the period 2004-09.